Postural weakness test using activforce device for regional muscle force in young volleyball athletes - Kesler, A.; Kahraman, Y. (Scientific Journal of Sport and Performance, 2025)
Postural weakness measurements are evaluated with hand dynamometer postural muscle testing to assess regional force range of motion. The aim of the study is to determine the strength and range of motion of young volleyball players according to peak and average force and regional muscle activation tests of 24 upper and lower body muscle groups. Subjects mean age 16 year participated in this study. Methodology was conducted activforce isometric muscle activation on examiner stability and proper measurement techniques. One and last (after 6 month) measured general force characteristics to determine peak and average force. Body peak force characteristics resulted large effect size, however, EF, EP, WE, WABD, KE, and AE not significant effect size. Body average force characteristics resulted large effect size, however, EF, WE, KE, AE not significant effect size with outcomes correlated on upper and lower body regional muscle force relationship. In this results can provide full body range of motion force production on testing condition to sport specific tasks, force measurements, postural weakness detection.